The power of circuit simulations for designing photonic integrated circuits. (21st July 2014) - Arellano, C.; Mingaleev, S. F.; Sokolov, E. S.; Richter, A.; Bartolini, Sandro; García, José M.; Pierson, Jean‐Marc; Dittman, Lars; Da Costa, Georges
SUMMARY The emerging of circuit‐level simulators for photonic integrated circuits (PICs) is driven by recent developments in technologies for integration of large‐scale monolithic PICs in both, silicon and InP technologies. For that reason, powerful circuit‐level simulators should be capable to model on the same circuit different types of sub‐components performing photonic, electronic or opto‐electronic, active or passive functions. In comparison with device‐level simulations, the use of realistic circuit‐level abstracted models facilitates rapid functional design without going into technological fabrication details and subsequent design flow. This accelerates the design process and decreases the number of runs to achieve the desired results. Detailed physical modeling remains limited to the design of some specific individual sub‐elements. Large‐scale PICs might comprise several thousands of elements. The circuit‐level abstraction also ensures that the simulation speed to achieve a certain simulation accuracy decreases reasonably slowly with the total number of photonic components in the modeled PIC. In this work, we present our solution for modeling PICs in the framework of the circuit‐level simulation tool VPIcomponentMaker™Photonic Circuits (Carnotstr. 6, 10587, Berlin, Germany, www.VPIphotonics.com). We demonstrate the combination of different simulation approaches in time domain, frequency domain and time‐and‐frequency domain for fast and accurate simulations. We discuss several diverse modeling benefits by means of application examples on silicon photonic PICs. Copyright © 2014 John Wiley & Sons, Ltd.